2013
DOI: 10.1002/latj.201390004
|View full text |Cite
|
Sign up to set email alerts
|

Laser Structuring of Flexible Organic Solar Cells

Abstract: Besides the „classical”︁ inorganic solar cells based on silicon, research on novel solar cell technologies has been intensified in the last years. The focus has been put especially on organic solar cells (OPV). Their industrial production has been made possible only recently.Organic solar cells constitute an alternative to common mono‐ and polycrystalline solar cells as well as the novel thin‐film technologies. Silicon, CIS/CIGS (Copper‐Indium‐Gallium‐Selenide) and Cadmium Telluride (CdTe) are used as semicond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Devices based on microelectromechanical systems (MEMS) are used in various applications, including electronics, information technology, biomedicine, and energy‐harvesting systems. As an alternative to the conventional photobeam/e‐beam‐/ion‐beam lithography techniques, laser direct structuring/writing (LDS/LDW) has attracted considerable interest as a simple, maskless, low‐cost method for fabricating 2D and 3D structures of different metals and their oxides . Recently, LPKF Laser & Electronics AG has demonstrated a precise and effective LDS method to produce microstructured layouts.…”
Section: Recent Progress and Advances In Laser Processing Of Metal Oxmentioning
confidence: 99%
“…Devices based on microelectromechanical systems (MEMS) are used in various applications, including electronics, information technology, biomedicine, and energy‐harvesting systems. As an alternative to the conventional photobeam/e‐beam‐/ion‐beam lithography techniques, laser direct structuring/writing (LDS/LDW) has attracted considerable interest as a simple, maskless, low‐cost method for fabricating 2D and 3D structures of different metals and their oxides . Recently, LPKF Laser & Electronics AG has demonstrated a precise and effective LDS method to produce microstructured layouts.…”
Section: Recent Progress and Advances In Laser Processing Of Metal Oxmentioning
confidence: 99%
“…The same can be said about procedures developed in the organic photovoltaics (OPVs) field. Many recent developments to optimize laser processing of PV modules based on organic semiconductors have been reported in the literature, which should enable the high‐throughput manufacture of these thin‐film modules, whilst ensuring high geometrical aperture ratios . Inactive or dead areas as low as 200 μm have been reported, with module geometrical aperture ratios larger than 90–97%.…”
Section: Discussionmentioning
confidence: 99%
“…The on-the-fly method for synchronizing a laser galvanometer scanner and a linear stage for quick and wide area fabrication could be promising in this direction [ 130 ]. Moreover, the roll-to-roll technique [ 131 ] could be a good candidate, too, for helping laser processing to become an enabling technology for the manufacture of anti-icing surfaces at an industrial scale. However, no studies on large-scale laser texturing for anti-icing could be found in the literature.…”
Section: Fabrication Of Superhydrophobic Surfaces With Anti-icing mentioning
confidence: 99%